ANALYSIS OF THE DEVELOPMENT OF THE ENTERPRISE AS A COMPLEX SYSTEM IN CONDITIONS OF INSTABILITY - KHAKHALIEV, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the conditions of modern management, the sustainable development of the enterprise becomes a key factor in increasing its efficiency in the process of digitalization, ensuring survival in conditions of uncertainty, crises and risks. Therefore, research in this area needs more attention. The work of both domestic and foreign scientists is devoted to issues of strategic management, existing problems related to the strategic analysis of the enterprise environment. Their work laid the foundation for the development of modern management methods that can be used by businesses to ensure sustainability and adaptability in today’s world. However, given the transformation of the country’s economy, these aspects require more in-depth study and adaptation to modern conditions and challenges. The article is devoted to the analysis of the enterprise as a complex system in conditions of instability. It has been proven that this approach is critically important and allows enterprises to respond more effectively to the challenges of the modern business environment, adapt to changes and ensure sustainable growth even in the most difficult conditions. The main components of the system analysis of the sustainability of the enterprise are substantiated, which include: assessment of the external environment, internal analysis, identification of risks and opportunities, development of strategies for sustainable development, and monitoring and adaptation. It was determined that thanks to the systemic approach, the enterprise can not only survive in conditions of instability, but also strengthen its position on the market. It is important that such an analysis allows taking into account a wide range of factors, providing a comprehensive view of the activities of enterprises. This helps to avoid isolated solutions that may only be effective in the short term but do not ensure long-term success.